Financial Strain and Prenatal Depression Among Pregnant Women in Ibadan, Nigeria: Mediating Pathways of Intimate Partner Violence, Food Insecurity, and Social Support - Wellington, Olubukola A. (European Journal of Mental Health, 2023)
Introduction: Although mothers’ mental health is receiving more attention, little remain known about the impact that financial strain may have on the mental health of expectant mothers. This is crucial in low- and middle-income countries because vulnerable populations are disproportionately affected by high rates of poverty, insufficient social safety nets, and unstable economies.Aims: This study examined the potential role that financial strain may play in prenatal depression while also taking into account the potential mediating roles of food insecurity, intimate relationship violence, and social support.Methods: To gather the data, a cross-sectional survey of 519 pregnant women in the second and third trimesters were selected methodically from a pool of women awaiting routine antenatal care from one primary health care center in each of the five urban local government areas of Ibadan metropolis. The Edinburgh Postnatal Depression Scale was used to measure prenatal depression. Using parallel and serial mediation models, the relationship between the variables – financial strain, intimate partner violence, food insecurity, social support, and prenatal depression – was examined.Results: Of the participants in this study, 28.1% reported having symptoms of depression during their pregnancy. The results also show that prenatal depression and financial strain are related, with each of the three mediators operating in a parallel and sequential causal order. The results of the mediation point to a causal chain with moderate effects.Conclusions: Interventions should evaluate the effects of integrating mental health services and social needs assessments into antenatal and primary health care.